Peri-transplant management of nonalcoholic fatty liver disease in liver transplant candidates - Samji, Naga Swetha; Heda, Rajiv; Satapathy, Sanjaya K. (Translational Gastroenterology and Hepatology; Vol 5 (January 2020): Translational Gastroenterology and Hepatology, 2019)
The incidence of non-alcoholic fatty liver disease (NAFLD) is rapidly growing, affecting 25% of the world population. Non-alcoholic steatohepatitis (NASH) is the most severe form of NAFLD and affects 1.5% to 6.5% of the world population. Its rising incidence will make end-stage liver disease (ESLD) due to NASH the number one indication for liver transplantation (LT) in the next 10 to 20 years, overtaking Hepatitis C. Patients with NASH also have a high prevalence of associated comorbidities such as type 2 diabetes, obesity, metabolic syndrome, cardiovascular disease, and chronic kidney disease (CKD), which must be adequately managed during the peritransplant period for optimal post-transplant outcomes. The focus of this review article is to provide a comprehensive overview of the unique challenges these patients present in the peritransplant period, which comprises the pre-transplant, intraoperative, and immediate postoperative periods.